Circular - Ayres, Frank
035-0088-001 International Brigade Association SAM WILD (President I.B.A.) Commander British Battalion MALCOLM DUNBAR (Vice-President I.B.A.) Chief of Staff 15th Brigade JACK BRENT (Hon. Secretary I.B.A.) 144 HOLBORN, E.C.1 (Entrance in Brooke Street) Holborn 2583 June 24th, 1943. Dear Comrade, In the past weeks the part that the Spanish fascist government is playing alongside Hitler and Mussolini has become more evident than ever before. After the blows of the United Nations at Stalingrad and Tunis, and with the prospect of heavier blows to come, Franco is attempting to gain a breathing space for his masters in Rome and Berlin. It is in this situation that we shall commemorate the anniversary of July 19th, 1936, that day when the international fascist gangsters first showed their hand as the enemies of democracy, not only in Germany and Italy, but the world over. On July 19th, 1936, Franco with the support of Hitler and Mussolini declared war against the legally elected government of Spain. Due to the lack of vigilance of the democracies, the Spanish people were defeated. Today, seven years since that war began, over a million people still languish in Franco jails, while the puppet dictator dares to give us lessons in humanity. BUT THE SPANISH PEOPLE WILL RISE AGAIN. The spirit of the Spanish People's Army is not dead. The flame of that international democratic solidarity which was embodied in the International Brigades, burns brighter than ever. We shall celebrate the anniversary of this glorious epic of the Spanish people at a MASS MEETING to be held at the CONWAY HALL, Red Lion Square, W.C.1 on MONDAY, JULY 19TH at 7.30 P.M. Representatives of the peoples' movements in Franco, Belgium, Poland and Yugo-Slavia will speak together with leading British M.P.'s, Trade Unionists and Labour Leaders. The Spanish representative will be JOVIAN SOLER, a man with a price on his head for his work in the democratic cause. The well-known SPANISH CHOIR of B.B.C. fame will give selections of Spanish songs. The INTERNATIONAL BRIGADE ASSOCIATION extends a hearty invitation to all those who have supported us in the past, and particularly to the members of the Labour movement, to be present at this memorable ANNIVERSARY MEETING. Men and women who have participated in the underground struggle of the peoples of Europe will tell you of their experiences, and you will hear how even in Spain, the SPANISH PEOPLE FIGHT ON THE SIDE OF DEMOCRACY. An account will be given of the results to date of our campaign for the RELIEF AND RELEASE of all members of the INTERNATIONAL BRIGADES who have been interned or imprisoned in FRANCE, SPAIN and N. AFRICA. The Division of Public Welfare and Relief at Allied Forces H.Q. has so far distributed nearly 100,000 francs to our men. Much more remains to be done and a COLLECTION WILL BE TAKEN at the meeting to carry on this work. We appeal to all organisations in particular to help us once more. WE MUST NOT FAIL in our duty to these first victims of fascist aggression. Yours fraternally, FRANK AYRES - London Secretary. 292/946/35/88